"Please Don't Let Academia Forget about Us:" An Exploration of Nursing Home Social Work Experiences during COVID-19. Issue 4 (19th May 2022) - Miller, Vivian J.; Anderson, Keith; Fields, Noelle L.; Kusmaul, Nancy
ABSTRACT: Nursing home social workers are on the frontlines during COVID-19 responding to individual resident needs, the needs of staff, and larger health needs of the nursing home. However, it is unclear whether nursing home social workers feel adequately trained and prepared in responding to disasters, such as COVID-19. To explore this, we used a study cross-sectional survey distributed via social media focusing on 1) prior training on disaster preparedness, 2) any content social workers wish had been a part of their education, and 3) suggestions for educators/academics to serve social workers on the frontlines. Data in this study are based on a sample of 63 (N=63) nursing home social workers. Demographic data were analyzed using SPSS and qualitative data were analyzed using the RaDar (rigorous and accelerated data reduction) technique. Findings revealed that most social workers had little to no training in disaster preparedness, and shared areas of future education initiatives. Participants also shared the need for bridging the research to practice gap through open access articles and support from academics. Findings from the present study reveal areas social work programs can expand gerontology-focused course offerings. Additionally, developments promoting practitioner support from academics is worth consideration.